POTENTIAL IMPACTS OF CLIMATE CHANGE ON AGRICULTURAL PRODUCTION IN THE LONG XUYEN QUADRANGLE, VIETNAMESE MEKONG DELTA (Nativa, 2023)
Climate change and its impacts have become a serious and concerning global issue. The Vietnamese Mekong Delta, is identified as one of the deltas most adversely affected by climate change. This study aims to assess the potential impacts of climate change on seven major agricultural production systems in the Long Xuyen Quadrangle region within the Vietnamese Mekong Delta. Utilizing the Analytic Hierarchy Process (AHP) in conjunction with calculating climate change impact indices, the research classifies the degree of climate change impact on agriculture, aquaculture and forestry. The study results indicate that different agricultural production systems will experience varying impacts from climate change. For rice cultivation, flooding and drought are identified as the factors with the highest impact. Factors such as temperature increase, changes in rainfall and salinity intrusion have the most significant effects on aquaculture. In contrast, cultivated and natural forests in the research area are less affected by climate change. This assessment outcome could be highly valuable for policymakers in developing local agricultural development plans.Keywords: climate change effects; land use; rice cultivation; saline intrusion. Impacto potencial das alterações climáticas na produção agrícola no Quadrilátero Long Xuyen, Delta vietnamita do Mekong RESUMO: As alterações climáticas e os seus impactos tornaram-se uma questão global séria e preocupante. O Delta vietnamita do Mekong é identificado como um dos deltas asiáticos mais afetados pelas alterações climáticas. Este estudo visa avaliar os impactos das alterações climáticas em sete grandes sistemas de produção agrícola na região do Quadrilátero Long Xuyen, no Delta do Mekong, Vietnã. Utilizando o Processo de Hierarquia Analítica (AHP), em conjunto com o cálculo dos índices de impacto das alterações climáticas, a investigação classifica o grau de impacto das alterações climáticas na agricultura, aquicultura e silvicultura. Os resultados do estudo indicam que diferentes sistemas de produção agrícola sofrerão impactos variados das alterações climáticas. Para o cultivo do arroz, as inundações e a seca são identificadas como os fatores de maior impacto. Fatores como o aumento da temperatura, as mudanças nas chuvas e a intrusão de salinidade têm os efeitos mais significativos na aquicultura. Em contraste, as florestas cultivadas e naturais na área de investigação são menos afetadas pelas alterações climáticas. O resultado desta avaliação poderá ser altamente valioso para as decisões políticas no desenvolvimento de planos de desenvolvimento agrícola local.Palavras-chave: efeitos das alterações climáticas; uso da terra; cultivo de arroz; intrusão salina.